2016
DOI: 10.1111/epi.13318
|View full text |Cite
|
Sign up to set email alerts
|

Seizures as presenting and prominent symptom in chorea‐acanthocytosis with c.2343del VPS13A gene mutation

Abstract: Objective: The aim of the study was to characterize the clinical features of nine patients in three families with chorea-acanthocytosis (ChAc) sharing the same rare c.2343del mutation in the VPS13A gene. Methods: Genetic test results, clinical description, magnetic resonance imaging (MRI), and electroencephalography (EEG), as well as laboratory results are summarized. Results: ChAc is a rare genetic disorder characterized by hyperkinetic movements, seizures, cognitive decline, neuropsychiatric symptoms, and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…In comparison, orofacial and oromandibular chorea are typical symptom in both affected patients in our study, but the presenting symptom in patient 1 is GTCS while in patient 2 is bruxism (see Tables 1 , 2 ). Given the novel and disparate VPS13A gene mutations identified in patient 1 and patient 2, it can be presumed that particular incipient symptoms may be associated with some specific VPS13A mutations, just as corroborated by the relevance of c.2343del mutation to epilepsy in Israeli families (Benninger et al, 2016). Nevertheless, restricted by the sample sizes in this study, it is imperative to investigate the intriguing proposition of genotype–phenotype correlation in larger ChAc groups in future study.…”
Section: Discussion and Literature Reviewmentioning
confidence: 91%
See 4 more Smart Citations
“…In comparison, orofacial and oromandibular chorea are typical symptom in both affected patients in our study, but the presenting symptom in patient 1 is GTCS while in patient 2 is bruxism (see Tables 1 , 2 ). Given the novel and disparate VPS13A gene mutations identified in patient 1 and patient 2, it can be presumed that particular incipient symptoms may be associated with some specific VPS13A mutations, just as corroborated by the relevance of c.2343del mutation to epilepsy in Israeli families (Benninger et al, 2016). Nevertheless, restricted by the sample sizes in this study, it is imperative to investigate the intriguing proposition of genotype–phenotype correlation in larger ChAc groups in future study.…”
Section: Discussion and Literature Reviewmentioning
confidence: 91%
“…In general, seizure are mostly antiepileptic drugs (AEDs) sensitive GTCS in ChAc, just as proven in patient 1, but simple and complex partial seizures have been described as well (Al-Asmi et al, 2005; Walker et al, 2007). For example, a recent study had identified a rare c.2343del VPS13A gene mutation in three Israeli families, in which most affected individuals presented seizures as the first and dominant symptom (Benninger et al, 2016). Moreover, seizures of this type could be of temporal lobe origin and were AEDs resistant in five out of nine patients (Benninger et al, 2016).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations